The regular Newton-Raphson method is initialized with a starting point $x_0$ and then you iterate $x_{n+1}=x_n-\dfrac{f(x_n)}{f'(x_n)}$.

In higher dimensions, there is an exact analog. We define:

$$F\begin{bmatrix}x\\y\\z\end{bmatrix} = \begin{bmatrix}f_1(x,y,z) \\ f_2(x,y,z) \\ f_3(x,y,z)\end{bmatrix} = \begin{bmatrix}\sqrt{(x-20000)^2+(y-19400)^2+(z-19740)^2}-20000 = 0 \\ \sqrt{(x-18700)^2+(y-1800)^2+(z-18500)^2}-19000 = 0 \\ \sqrt{(x-18900)^2+(y-17980)^2+(z-20000)^2}-19500= 0 \end{bmatrix}$$

The derivative of this system is the $3x3$ Jacobian given by:

$J(x,y,z) = \begin{bmatrix} \dfrac{\partial f_1}{\partial x} & \dfrac{\partial f_1}{\partial y} & \dfrac{\partial f_1}{\partial z}\\ \dfrac{\partial f_2}{\partial x} & \dfrac{\partial f_2}{\partial y} & \dfrac{\partial f_2}{\partial z} \\ \dfrac{\partial f_3}{\partial x} & \dfrac{\partial f_3}{\partial y} & \dfrac{\partial f_3}{\partial z}\end{bmatrix} =\\ \begin{bmatrix} \frac{x-20000}{\sqrt{(x-20000)^2+(y-19400)^2+(z-19740)^2}} & \frac{y-19400}{\sqrt{(x-20000)^2+(y-19400)^2+(z-19740)^2}} & \frac{z-19740}{\sqrt{(x-20000)^2+(y-19400)^2+(z-19740)^2}} \\ \frac{x-18700}{\sqrt{(x-18700)^2+(y-1800)^2+(z-18500)^2}} & \frac{y-1800}{\sqrt{(x-18700)^2+(y-1800)^2+(z-18500)^2}} & \frac{z-18500}{\sqrt{(x-18700)^2+(y-1800)^2+(z-18500)^2}} \\ \frac{x-18900}{\sqrt{(x-18900)^2+(y-17980)^2+(z-20000)^2}} & \frac{y-17980}{\sqrt{(x-18900)^2+(y-17980)^2+(z-20000)^2}} & \frac{z-20000}{\sqrt{(x-18900)^2+(y-17980)^2+(z-20000)^2}} \\ \end{bmatrix}$

The function $G$ is defined as:

$$G(x) = x - J(x)^{-1}F(x)$$

and the functional Newton-Raphson method for nonlinear systems is given by the iteration procedure that evolves from selecting an initial $x^{(0)}$ and generating for $k \ge 1$,

$$x^{(k)} = G(x^{(k-1)}) = x^{(k-1)} - J(x^{(k-1)})^{-1}F(x^{(k-1)}).$$

We can write this as:

$$\begin{bmatrix}x^{(k)}\\y^{(k)}\\z^{(k)}\end{bmatrix} = \begin{bmatrix}x^{(k-1)}\\y^{(k-1)}\\z^{(k-1)}\end{bmatrix} + \begin{bmatrix}y_1^{(k-1)}\\y_2^{(k-1)}\\y_3^{(k-1)}\end{bmatrix}$$

where:

$$\begin{bmatrix}y_1^{(k-1)}\\y_2^{(k-1)}\\y_3^{(k-1)}\end{bmatrix}= -\left(J\left(x^{(k-1)},y^{(k-1)},z^{(k-1)}\right)\right)^{-1}F\left(x^{(k-1)},y^{(k-1)},z^{(k-1)}\right)$$

Here is a starting vector:

$$x^{(0)} = \begin{bmatrix}x^{(0)}\\y^{(0)}\\z^{(0)}\end{bmatrix} = \begin{bmatrix}1\\1\\1\end{bmatrix}$$

The iterates will be:

  • $x_0 = (1,1,1)$
  • $x_1 = (17289.9,15734.3,-8508.52)$
  • $x_2 = (13614.9,9566.68,1369.85)$
  • $x_3 = (16370.9,11019.8,1760.91)$
  • $x_4 = (16274.,10923.6,2010.87)$
  • $x_5 = (16276.2,10924.5,2011.53)$
  • $x_6 = (16276.2,10924.5,2011.53)$

You should end up with a solution that looks something like:

$$\begin{bmatrix}x\\y\\z\end{bmatrix} = \begin{bmatrix} 16276.2 \\ 10924.5 \\ 2011.53 \end{bmatrix}$$

Of course, for a different starting vector you could get a different solution and perhaps no solution at all.


I think that you can make the problem simpler the solution of which not requiring Newton-Raphson or any root finder method; the solution is explicit and direct (it does not require any iteration).

Start squaring the expressions to define $$f_i={(x-x_i)^2+(y-y_i)^2+(z-z_i)^2}-r_i^2=0$$ Now, develop $(f_2-f_1)$ and $(f_3-f_2)$ for example. As a result, you have two linear equations since terms $x^2,y^2,z^2$ disappear. You can solve these two equations for $y$ and $z$ and the result will write $y=\alpha_1+\alpha_2 x$,$z=\beta_1+\beta_2 x$. Report these expressions in $f_1$ which is a quadratic equation in $x$.

Using the numbers you gave, I found $$y=\frac{121160315}{7921}-\frac{4255 }{15842}x$$ $$z=-\frac{340394455}{7921}+\frac{43785 }{15842}x$$ and the solution of $f_1=0$ is just $x=16276.24775$ from which $y=10924.45372$, $z=2011.526168$ (just as Amzoti found).

You must take care that there is a second root for the quadratic $x=27858.39152$ from which $y=7813.607758$, $z=34022.89878$.

Depending on the starting point chosen for Newton-Raphson, you would arrive to one of these two solutions.